Development of graphical user interface for finite element analysis of static loading of a column using MATLAB (2010)
In this work, the capability of MATLAB software package to develop graphical user interface (GUI) package was demonstrated. A GUI was successfully developed using MATLAB programming language to study the behaviour of a suspended column under uniaxial static loading by solving the numerical model created based on the finite element method (FEM). The comparison between the exact solution from previous researches and the numerical analysis showed good agreement. The column average strain, average stress and average load are equivalent but more accurate to the ones obtained when the whole column is taken as one element (two nodes for one dimensional linear finite element problem). It was established in this work that MATLAB is not only a software package for numerical computation but also for application development.